Corporate Governance and Financial Distress: Empirical Evidence of Energy Sector Companies on the Indonesia Stock Exchange - Debora, Dea Niken; Zoraya, Intan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The present paper is an empirical analysis of the impact of corporate governance on financial distress in companies listed on the Indonesia Stock Exchange (IDX) over the period from 2016 to 2023. Financial distress is measured by the Altman Z-score model. Variables of corporate governance include institutional ownership, managerial ownership, the ratio of independent commissioners, and board size. The sample consisted of 107 companies. Multiple linear regression was used to analyze the data. The results proved that institutional ownership and managerial ownership do not significantly affect financial distress. On the other hand, it was found that independent commissioners and board size have a considerable negative impact to, while the board of commissioners has a positive impact. Among the control variables, Leverage is negatively significant, whereas firm size is highly significant.